URGENSI PSIKOLOGI DALAM AKTIVITAS DAKWAH - Silvia Riskha Fabriar (An-Nida : Jurnal Komunikasi Islam, 2019)
Abstract Da’wah is an Islamic communication, which is a communication activity carried out intentionally and consciously in the form of an invitation to the path of God with amar ma'ruf nahi munkar to achieve the happiness of humanity in the world and the hereafter. When preaching, the preacher needs to even have to know the psychological condition of the object being preached (mad'u) so that what is conveyed can later be conveyed properly. In this case, psychology provides a way to convey material and establish methods of preaching to humans who are totality (psychophysical) creatures and have personalities from both internal and external influences. Thus, psychology in the process of da'wah has a focal point in the knowledge of human behavior. Based on psychiatric or psychological elements, the process of preaching will proceed according to the needs that are expected of humans as individuals and social beings. Keywords: da’wah, communication, psychology condition Dakwah merupakan suatu komunikasi Islam, yaitu suatu aktivitas komunikasi yang dilakukan secara sengaja dan sadar yang berupa ajakan kepada jalan Allah dengan amar ma’ruf nahi munkar untuk meraih kebahagiaan manusia dunia dan akhirat. Ketika berdakwah, da’i perlu bahkan harus mengetahui kondisi psikologis objek yang didakwahi (mad’u) agar apa yang disampaikan nantinya dapat tersampaikan dengan baik. Dalam hal ini, psikologi memberikan jalan bagaimana menyampaikan materi dan menetapkan metode dakwah kepada manusia yang merupakan makhluk totalitas (psikofisik) dan memiliki kepribadian baik dari faktor dalam maupun pengaruh dari luar. Dengan demikian, psikologi dalam proses dakwah mempunyai titik perhatian pada pengetahuan tentang tingkah laku manusia. Dengan berlandaskan unsur-unsur kejiwaan atau psikologi, proses dakwah akan berjalan sesuai kebutuhan yang diharapkan manusia sebagai individu dan makhluk sosial. Kata kunci: dakwah, komunikasi, kondisi psikologis